Model Keperawatan Keluarga Santun Lansia dalam Upaya Peningkatan Kualitas Asuhan Keluarga pada Lansia: A Literature Review - Etty Rekawati; Achir Yani S. Hamid; Junaiti Sahar; Widyatuti Widyatuti; Ni Luh Putu Dian Yunita Sari (FORIKES, 2019)
Family is the closest person to the elder person who has an important role in caring for elder person. The purpose of this study is to provide an overview of the cordial older family nursing model in an effort to improve the quality of family care in elder person. The study approach was the study of literature with expert agreement. The search method for library resources was done online, which uses databases such as Science Direct, Scopus, Sage, Pubmed and ProQuest. The keywords used were